Unveiling the role of soil in urban vegetation greenness: City-scale evidence from field sampling across green spaces in Shanghai - Hanxin Tang; Mengyao Ci; Quanbo Yu; Shuyi Zhang; Ruoxi Lin; Junjie Ruan; Qicheng Zhong; Min Liu (Journal of Cleaner Production, 2026)

Enzyme-programmed cellulose nanocrystal interfaces: Regulating degradation microenvironment and plant growth of polylactic acid films - Ruoxi Nie; Somia Yassin Hussain Abdalkarim; Bunan Wu; Haibin Ji; Chaopei Chen; Haicheng Huang; Hou-Yong Yu (Journal of Hazardous Materials, 2026)

piR-16404 drives ferroptotic liver injury via CASTOR1/mTORC1/GPX4 dysregulation in HepG2 cells and mice: a novel toxicity mechanism of N, N-dimethylformamide - Wanli Ma; Xiaoyu Huo; Ruoxi Li; Jingjing Xing; Lin Xu; Dianke Yu (Archives of Toxicology, 2026)

The synergistic effects of Lactobacillus casei HDS-01-konjac glucomannan synbiotic: probiotic potential and in vitro fecal fermentation - Shan Yu; Yingying Ning; Jiaju Xu; Ruoxi Yang; Dan Zhao (Food Research International, 2025)

High-valent copper species induced degradation of naprosyn in zero-valent copper-stimulated monopersulfate system with hydroxylamine and neocuproine as accelerators - Xin Liu; Quan Yu; Peng Xu; Ruoxi Wu; Baolin Hou; Mengqi Zheng (Process Safety and Environmental Protection, 2025)

A data-driven method in predicting crack coalescence based on pre-existing flaw geometry - Chunjiang Zou; Boyuan Chen; Huakun Yu; Sihan Yan; Ruoge Wang; Ruoxi Zhu; Yunshun Li; Daokun Zhang (Engineering Geology, 2025)

The inhibition potentiality of sodium carboxymethyl cellulose on PhIP, Harman, and Norharman formation of fried beef patties at low NaCl level - Yi Zhao; Pinghua Deng; Ruoxi Ma; Shuang Teng; Hang Lu; Zheng Liu; Haotian Yu; Yawei Zhang (Meat Science, 2025)

Functionalization of slow-release fertilizers and “passive predation microplastics” mechanism for polylactic acid composites - Haibin Ji; Somia Yassin Hussain Abdalkarim; Ruoxi Nie; Hou-Yong Yu (Journal of Hazardous Materials, 2025)

A review of automatic sleep stage classification using machine learning algorithms based on heart rate variability - Ruoxi Yu; Yan Li; Kangqing Zhao; Fangfang Fan (Sleep and Biological Rhythms, 2025)

Bridging the buried interface with conjugated molecule for highly efficient carbon-based inorganic CsPbI2Br perovskite solar cells fabricated in air - Yifei Shi; Lei Zhang; Shuming Hu; Xu Wang; Jiajia Han; Jincheng Huang; Junjie Chen; Yuanfang Zhang; Xinlong Zhang; Jintao He; Hengzhi Zuo; Jiayao Ju; et al. (Chemical Engineering Journal, 2024)

Correction: Toxic effects of atmospheric deposition in mining areas on wheat seedlings - Yu Xiao; Huijun Luan; Shougan Lu; Mingjie Xing; Chunying Guo; Ruoxi Qian; Xin Xiao (Environmental Geochemistry and Health, 2024)

A MYB transcription factor GhTT2 of Gossypium hirsutum regulates proanthocyanidin accumulation and improves osmotic tolerance in Arabidopsis - Jun Mei; Rongrong Mu; Qingqing Niu; Huimin Zhu; Ruoxi Chen; Xiaomiao Cai; Meng Miao; Dongliang Yu; Liping Ke; Yuqiang Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Toxic effects of atmospheric deposition in mining areas on wheat seedlings - Yu Xiao; Huijun Luan; Shougan Lu; Mingjie Xing; Chunying Guo; Ruoxi Qian; Xin Xiao (Environmental Geochemistry and Health, 2024)

Online and offline cooperation promotion mechanism in the E-waste recycling industry - Gang Tian; Ziyi Xia; Ruoxi Tian; Huaping Sun; Liping Yu; Dongyin Sun (Environmental Impact Assessment Review, 2024)

Distribution and transformation of potentially toxic elements in crack under coal mining disturbance - Junchi Li; Qinxue Yu; Ruoxi Qian; Xin Xiao; Yan Liang; Ping Luo; Hui Wang; Yin Lu; Lili Xu; Qingfeng Liu; Yu Xiao (Environmental Monitoring and Assessment, 2023)

A phytoexclusion strategy for reducing contamination risk of rice based on low-Cd natural variations pyramid of root transporters - Yan Huili; Liu Ruoxi; Peng Zhimei; Zhang Hezifan; Hao Shuangnan; Guo Hanyao; Wang Binghan; Wang Weiping; Yu Yijun; Zhang Hongliang; Qian Tonghui; Xu Wenxiu; et al. (Journal of Hazardous Materials, 2023)

Responsibility disengagement or sharing? Cooperative fulfilling mechanism of solid waste management in the remanufacturing supply chain - Gang Tian; Yaru Zhang; Ruoxi Tian; Yu Gong; Huaping Sun; Liang Li; Shaoqing Geng (Environmental Science and Pollution Research, 2023)

Downregulation of the paired box gene 3 inhibits the progression of skin cutaneous melanoma by inhibiting c-MET tyrosine kinase - Kun Zhang; Chunfang Yu; Ruoxi Tian; Wancong Zhang; Shijie Tang; Guiying Wang (Molecular Biology Reports, 2022)

Gene expression signatures for phlegm-dampness constitution of Chinese medicine - Lingru Li; Juan Feng; Haiqiang Yao; Lan Xie; Yu Chen; Lingling Yang; Shujuan Hou; Shipeng Zhao; Ranran Sun; Yanling Wu; Tongtong Bai; Yingshuai Li; et al. (Science China Life Sciences, 2017)

Age polyethism drives community structure of the bacterial gut microbiota in the fungus‐cultivating termite O dontotermes formosanus - Hongjie Li; Carsten Dietrich; Na Zhu; Aram Mikaelyan; Bin Ma; Ruoxi Pi; Yu Liu; Mengyi Yang; Andreas Brune; Jianchu Mo (Environmental Microbiology, 2016)
Summary Fungus‐cultivating termites ( M acrotermitinae) possess an elaborate strategy of lignocellulose digestion. It involves a lignocellulose‐degrading fungal symbiont (genus T ermitomyces ), a diverse gut microbiota and a characteristic labour division in food processing. In this study, using pyrotag sequencing and electron microscopy, we analysed the bacterial microbiota in the hindgut of O dontotermes formosanus and its fungus comb to investigate the spatial organization, establishment and temporal succession of the bacterial communities colonizing specific microhabitats. Our results document strong differences between the communities at the hindgut epithelium and the luminal fluid of newly moulted, young and old worker termites. The differences in community structure were consistent with the density, morphology and spatial distribution of bacterial cells and the pools of microbial metabolites in the hindgut compartment, underlining that both gut development and the age‐specific changes in diet affect the composition and functional role of their gut microbiota. These findings provide strong support for the concept that changes in diet and gut environment are important determinants of community structure because they create new niches for microbial symbionts.